PENGARUH AKURASI KODING TERHADAP HASIL PENGAJUAN KLAIM RAWAT INAP BPJS KESEHATAN DI RS SENTRA MEDIKA CIBINONG - Lestari, Jayanti; Muchlis, Husni Abdul; Hosizah, Hosizah; Temesvari, Nauri Anggita (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Claim files that are returned / pending can result in a decrease in hospital income due to a mismatch in service costs with the number of claims billed. The results of submitting inpatient claims at Sentra Medika Cibinong Hospital in September-November 2023 were 327 (10%) pending files out of 3,250 files billed. The purpose of the study was to determine the effect of coding accuracy on the results of submitting BPJS Health inpatient claims. With a quantitative approach and cross sectional design. The population was all inpatient claim files, a sample of 300 claim files with the Accidental Sampling technique. Data analysis using chi square test and observation data collection. The results showed inaccurate coding files 116 (38.7%) and accurate coding 184 (61.3%) and pending files 49 (16.3%) and not pending 251 (83.7%). While the results of the chi square test obtained a P-value of 0.002 <0.05 OR value of 2.733 It was concluded that there was an influence between coding accuracy on the results of submitting BPJS Health inpatient claims at Sentra Medika Cibinong Hospital. Furthermore, inaccurate coding accuracy files are 2.7 times more likely to be pending than accurate files. Accurate coding files were pending 20 (10.9%) and not pending 164 (89.1%), inaccurate coding files were pending 29 (25%) and not pending 87 (75%). Suggestions for conducting regular evaluations of cases that have the potential to experience pending claims. Keyword: Coding Accuracy, Submission Results, Pending Claims Abstrak: Berkas klaim yang dikembalikan/pending dapat mengakibatkan penurunan pendapatan rumah sakit akibat ketidaksesuaian biaya layanan dengan jumlah klaim yang ditagihkan. Hasil pengajuan klaim rawat inap di RS Sentra Medika Cibinong pada bulan September–November 2023 Sebanyak 327 (10%) berkas pending dari 3.250 berkas yang ditagihkan. Tujuan penelitian untuk mengetahui pengaruh akurasi koding terhadap hasil pengajuan klaim rawat inap BPJS Kesehatan. Dengan pendekatan kuantitatif dan desain cross sectional. Populasi seluruh berkas klaim rawat inap pada bulan Maret 2024, sampel 300 berkas klaim dengan teknik Accidental Sampling. Analisa data menggunakan uji chi square dan pengumpulan data observasi. Hasil penelitian menunjukan berkas koding tidak akurat 116 (38,7%) dan koding akurat 184 (61,3%) serta berkas terpending 49 (16,3%) dan tidak terpending 251 (83,7%). Sedangkan hasil uji chi square diperoleh nilai P-value 0,002 < 0,05 nilai OR 2,733 Maka disimpulkan ada pengaruh antara akurasi koding terhadap hasil pengajuan klaim rawat inap BPJS Kesehatan di RS Sentra Medika Cibinong. Selanjutnya berkas akurasi koding tidak akurat berpeluang 2,7 kali akan terpending dibandingkan berkas yang akurat. Berkas koding akurat yang terpending 20 (10,9%) dan tidak terpending 164 (89,1%), berkas koding tidak akurat yang terpending 29 (25%) dan tidak terpending 87(75%). Saran melakukan evaluasi secara berkala terhadap kasus yang berpotensi mengalami pending klaim. Kata kunci: Akurasi Koding; Hasil Pengajuan; Pending Klaim